2013
DOI: 10.1159/000351865
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy Partially Mediates between Social Support and Health-Related Quality of Life in Family Caregivers for Dementia Patients in Shanghai

Abstract: Background: There is a paucity of research assessing health-related quality of life (HRQoL) and self-efficacy in caregivers of relatives with dementia in mainland China. Aims: To compare the level of HRQoL between caregivers and the general population in mainland China and to assess the role of caregiver self-efficacy in the relationship between caregiver social support and HRQoL. Methods: A cross-sectional study was conducted in Shanghai, China. The caregivers were recruited from the outpatient department of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
26
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 78 publications
8
26
0
5
Order By: Relevance
“…This result is consistent with reports stating that self-appraisal of self-efficacy predicts life satisfaction and less depression for family caregivers of patients with physical disability [31,32]. On the other hand, self-efficacy was reported to moderate the relationship between intervention condition and treatment outcome for family caregivers of patients with dementia [33], and to partially mediate the relationship between caregiver social support and HRQoL as well as that between behavioral problems and caregiver mental health [34]. Different roles of self-efficacy in predicting health outcomes for family caregivers of patients with VaD and AD need to be validated by future studies.…”
Section: Discussionsupporting
confidence: 86%
“…This result is consistent with reports stating that self-appraisal of self-efficacy predicts life satisfaction and less depression for family caregivers of patients with physical disability [31,32]. On the other hand, self-efficacy was reported to moderate the relationship between intervention condition and treatment outcome for family caregivers of patients with dementia [33], and to partially mediate the relationship between caregiver social support and HRQoL as well as that between behavioral problems and caregiver mental health [34]. Different roles of self-efficacy in predicting health outcomes for family caregivers of patients with VaD and AD need to be validated by future studies.…”
Section: Discussionsupporting
confidence: 86%
“…To reduce caregiver burden, more social support from professional health care institutions and personnel is needed, such as the provision of appropriate information and support by medical staff and the strengthening of family care services for caregivers. Moreover, selfefficacy can reduce caregiver burden [24,25], lead to more positive emotions and contribute to better physical health [26,27]. Our previous studies have also confirmed that self-efficacy reduces the burden of care for caregivers and leads to more positive emotions and better physical health [10].…”
Section: Discussionsupporting
confidence: 57%
“…Social support may greatly impact on caregivers' QoL, but most of the studies focus on caregivers of patients with neurological diseases such as dementia (27,28). In addition, when this dimension is taken into account with caregivers of patients with DOC (10)(11)(12), no specific assessment instruments have been used and there are no studies specifically aimed at assessing perceived social support in informal caregivers of patients with DOC.…”
Section: Introductionmentioning
confidence: 99%